Unique long terminal repeat U3 sequences distinguish exogenous jaagsiekte sheep retroviruses associated with ovine pulmonary carcinoma from endogenous loci in the sheep genome. - Bai, J (1996)
Ovine pulmonary carcinoma (OPC) is a contagious lung cancer of sheep that is presumed to be caused by an exogenous retrovirus of sheep, jaagsiekte sheep retrovirus (JSRV). The sheep genome carries 15 to 20 copies of endogenous sheep retrovirus (ESRV) loci that hybridize to JSRV DNA probes. In order to clarity the etiologic roles of ESRV and an exogenous JSRV-like retrovirus (exJSRV) in OPC, we assessed sequence differences between ESRV and JSRV. Molecular characterization of six ESRV loci revealed restriction sites specific for JSRV. Nucleotide sequences of ESRVs from sheep of different breeds were similar to those of JSRV in structural genes but divergent in U3. Therefore, primers specific for the U3 sequences of exJSRV were designed for use in the PCR. Of 13 tumor DNAs tested by PCR with these exogenous-virus U3 primers, 8 produced DNA fragments that hybridized with the JSRV gag probe, but neither lung DNAs from healthy sheep nor DNAs from nontumor tissues of diseased sheep produced similar DNA fragments. exJSRV PCR products from tumor DNAs of sheep with OPC from three continents had restriction profiles similar to each other but different from those of ESRVs upon digestion with EcoRI, HindIII, NdeI, KpnI, and ScaI. These exjSRVs could be classified into two genotypes according to U3 sequences and restriction profiles. U3 sequences of exJSRV proviruses in tumors strongly resembled those of JSRV but differed from those of ESRVs, suggesting that exJSRVs, rather than ESRVs, are primarily associated with oncogenesis in OPC.